Authenticity in Context: Being True to Working Selves. Issue 1 (March 2019) - Chen, Serena
The core premise of this article is that it is scientifically informative and psychologically meaningful to conceptualize and assess authenticity in context. I begin by providing some theoretical background on the nature of the self-concept, highlighting how the self-concept is composed of a collection of selves, with different selves activated and therefore at play in different contexts. This basic fact, that the self-concept is both multifaceted and malleable, implies that authenticity is a construct that requires study at a contextual level. I illustrate this by reviewing theory and findings from 3 areas of research, incorporating studies from my laboratory throughout. These areas are (a) authenticity in the context of close relationships; (b) authenticity in hierarchical contexts, wherein one occupies a lower versus higher position of social power; and (c) authenticity in relation to the larger cultural context. Finally, I address a number of issues and questions that arise when considering authenticity in context and propose a number of directions for future research on the context-specific nature of authenticity.